Inhibition of MicroRNA 6937 Delays Photoreceptor and Vision Loss in a Mouse Model of Retinitis Pigmentosa - Ander Anasagasti; Araceli Lara-López; Santiago Milla-Navarro; Leire Escudero-Arrarás; María Rodríguez-Hidalgo; Nerea Zabaleta; Gloria González Aseguinolaza; Pedro de la Villa; Javier Ruiz-Ederra (MDPI AG, 2020)
Inherited retinal dystrophies (IRDs) are a group of rare retinal conditions, including retinitis pigmentosa (RP), caused by monogenic mutations in 1 out of more than 250 genes. Despite recent advancements in gene therapy, there is still a lack of an effective treatment for this group of retinal conditions. MicroRNAs (miRNAs) are a class of highly conserved small non-coding RNAs that inhibit gene expression. Control of miRNAs-mediated protein expression has been described as a widely used mechanism for post-transcriptional regulation in many physiological and pathological processes in different organs, including the retina. Our main purpose was to test the hypothesis that modulation of a group of miRNAs can protect photoreceptor cells from death in the rd10 mouse model of retinitis pigmentosa. For this, we incorporated modulators of three miRNAs in adeno-associated viruses (AAVs), which were administered through sub-retinal injections. The results obtained indicate that inhibition of the miR-6937-5p slows down the visual deterioration of rd10 mice, reflected by an increased electroretinogram (ERG) wave response under scotopic conditions and significant preservation of the outer nuclear layer thickness. This work contributes to broadening our knowledge on the molecular mechanisms underlying retinitis pigmentosa and supports the development of novel therapeutic approaches for RP based on miRNA modulation.